Hubungan Kepadatan Parasit Terhadap Kadar Hemoglobin Pada Penderita Malaria Asimtomatik Di Gunung Sari - Agustin, Ermadiana; Resnhaleksmana, Ersandhi; Getas, I Wayan (Poltekkes Kemenkes Mataram, 2022)
Malaria is an infectious disease that still provides a high morbidity rate in the world. Malaria affects almost all blood components, one of which is hemoglobin levels. In malaria infection, there is a decrease in hemoglobin levels due to the destruction of excessive red blood cells by the malaria parasite. Asymptomatic malaria infection plays an important role in malaria transmission as it is a major influence on ongoing treatment-based malaria control programs. The research objective in this study was to know the effects of parasite density on hemoglobin levels in patients with Asymptomatic Malaria disease in Gunung Sari. The research study used is an analytic observational study with a Cross-Sectional approach with the Accidental sampling method and the Consecutive sampling method. The result of the study is out of the 14 samples diagnosed with asymptomatic malaria, 12 people (85.7%) had a mild degree of parasitemia based on parasite density calculations (8-800 / μl), and 2 people (14.3%) had moderate degrees of parasitemia (801- 8800 / μl). As many as 6 people (42.9%) had normal Hb levels, and 8 people (57.1%) had Hb levels below normal values. The conclusion of this study proved that there is a significant correlation between parasite density and hemoglobin levels in asymptomatic malaria patients in Gunung Sari.